(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
In this article the author studies in detail a current situation in using odor prints for solving and investigation of the crimes in the Socialist Republic of Vietnam. The study focuses on conducting a forensic examination of human odor prints for proving in criminal cases. The article also considers the experience in forensic studies of odor prints in the Russian Federation using special methods and detection dogs. The author especially contributed to the study of the topic by having considered the causes of this problem and developing recommendations for its solution to improve the effectiveness of the Ministry of Public Security of the Socialist Republic of Vietnam in the fight against the crime.